Catecismo Castellano - Cakchikel - Resines, Luis (Estudio agustiniano, 2021)
This article shows a unknown bilingual catechism, Spanish and Cakchiquel, language of Guatemala, dated perhaps at XVIII century. Two little books integrate it: a catechism, and a ritual for viaticum and marriage. The catechism have no author, may be a Franciscan friar. It have very disorder in its themes; and also is not complete, by absence of commandments. This a target for the complementary confessional book. It have a precedent in XVI century, in the catechism of bishop Francisco Marroquin.